Biotechnological Applications of Quorum Sensing Inhibitors (Springer Singapore, 2018)
This book discusses the practical applications of quorum sensing inhibitors for both human and plant health. Quorum sensing inhibitors that disrupt microbial biofilms can be employed to treat bacterial infections. The book describes the various bioactive molecules that can serve as quorum sensing inhibitors to combat deadly bacterial infections, in addition to several synthetic quorum sensing inhibitors. Quorum sensing is the mechanism through which bacteria develop antibiotic resistance. Intended to provide a clearer understanding of the practical applications of quorum sensing inhibitors, the book details how the problem of antibiotic resistance can be countered through the intelligent application of quorum sensing inhibitors.